2015
DOI: 10.1038/pcan.2014.52
|View full text |Cite
|
Sign up to set email alerts
|

Impact of metformin on clinical outcomes among men with prostate cancer: a systematic review and meta-analysis

Abstract: Background Conflicting evidence exists regarding the beneficial effects of metformin in prostate cancer. Objective To determine the association between metformin and clinical outcomes in prostate cancer using systematic review and meta-analysis. Methods Original articles published in English until third week of July, 2014 were searched in electronic databases (Medline-Ovid, Scopus, The Cochrane Library, Web of Science, ProQuest) for studies on metformin use in prostate cancer. The clinical outcomes assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 34 publications
1
42
0
3
Order By: Relevance
“…For prostate cancer, findings are less consistent. Five meta-analyses have examined the effect of metformin on OS [22, 23, 2527], two of which also investigated prostate CSS [25, 26]. Only two meta-analyses identified a significant benefit in OS [23, 25], with no benefit identified in prostate CSS.…”
Section: Discussionmentioning
confidence: 99%
“…For prostate cancer, findings are less consistent. Five meta-analyses have examined the effect of metformin on OS [22, 23, 2527], two of which also investigated prostate CSS [25, 26]. Only two meta-analyses identified a significant benefit in OS [23, 25], with no benefit identified in prostate CSS.…”
Section: Discussionmentioning
confidence: 99%
“…It is has been suggested that insulin resistance is associated with more advanced and aggressive PCa, while treatment with metformin reduces the risk of biochemical recurrence in patients with PCa (Raval et al 2015). Mechanistically, insulin resistance is accompanied by hyperinsulinemia, which leads to the inhibition of insulin-like growth factor (IGF) binding protein and finally increase of IGF1 (Luo & Murphy 1992, Aggarwal et al 2013.…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent meta-analyses have focused on the impact of metformin on site-specific cancer mortality and overall survival, as reviewed in Table 2 [26, 27, 35-43]. These analyses have shown marked reductions in cancer-specific mortality for colon, lung and early-stage prostate cancer, and improvements in overall survival for breast, colon, gynaecological (endometrial and ovarian), liver, lung, prostate, and pancreatic cancer.…”
Section: Epidemiological Evidencementioning
confidence: 99%